Training stress, neuromuscular fatigue and well-being in volleyball: a systematic review - Rebelo, A.; Pereira, J. R.; Cunha, P.; Coelho-e-Silva, M. J.; Valente-dos-Santos, J. (BMC Sports Science, Medicine and Rehabilitation, 2024)
Background Volleyball, with its unique calendar structure, presents distinct challenges in training and competition scheduling. Like many team sports, volleyball features an unconventional schedule with brief off-season and pre-season phases, juxtaposed against an extensive in-season phase characterized by a high density of matches and training. This compact calendar necessitates careful management of training loads and recovery periods. The effectiveness of this management is a critical factor, influencing the overall performance and success of volleyball teams. In this review, we explore the associations between training stress measures, fatigue, and well-being assessments within this context, to better inform future research and practice.